Thermodynamics of Coupled Folding in the Interaction of Archaeal RNase P Proteins RPP21 and RPP29 - Xu, Yiren (2012)
We have used isothermal titration calorimetry (ITC) to identify and describe binding-coupled equilibria in the interaction between two protein subunits of archaeal ribonuclease P (RNase P). In all three domains of life, RNase P is a ribonucleoprotein complex that is primarily responsible for catalyzing the Mg(2+)-dependent cleavage of the 5′ leader sequence of precursor tRNAs during tRNA maturation. In archaea, RNase P has been shown to be composed of one catalytic RNA and up to five proteins, four of which associate in the absence of RNA as two functional heterodimers, POP5-RPP30 and RPP21-RPP29. NMR studies of the Pyrococcus furiosus RPP21 and RPP29 proteins in their free and complexed states provided evidence for significant protein folding upon binding. ITC experiments were performed over a range of temperatures, ionic strengths, pH values and in buffers with varying ionization potential, and with a folding-deficient RPP21 point mutant. These experiments revealed a negative heat capacity change (ΔC(p)), nearly twice that predicted from surface accessibility calculations, a strong salt dependence to the interaction and proton release at neutral pH, but a small net contribution from these to the excess ΔC(p). We considered potential contributions from protein folding and burial of interfacial water molecules based on structural and spectroscopic data. We conclude that binding-coupled protein folding is likely responsible for a significant portion of the excess ΔC(p). These findings provide novel structural-thermodynamic insights into coupled equilibria that enable specificity in macromolecular assemblies.